2011
DOI: 10.1007/s10555-011-9317-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of the EP receptors for prostaglandin E2 in skin and skin cancer

Abstract: One of the most common features of exposure of skin to ultraviolet (UV) light is the induction of inflammation, a contributor to tumorigenesis, which is characterized by the synthesis of cytokines, growth factors and arachidonic acid metabolites, including the prostaglandins (PGs). Studies on the role of the PGs in non-melanoma skin cancer (NMSC) have shown that the cyclooxygenase-2 (COX-2) isoform of the cyclooxygenases is responsible for the majority of the pathological effects of PGE2. In mouse skin models,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 88 publications
(206 reference statements)
4
85
0
Order By: Relevance
“…In contrast, the EP3 receptor inhibits adenylate cyclase by coupling to Gi. 18,19 Nevertheless, the roles of EP subtypes in cell proliferation are different, and could be cell type-dependent. [20][21][22][23][24] To study the role of PGE 2 in myoblast proliferation, the expression of EPs in mouse primary myoblasts was determined showing that all EPs are expressed in myoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the EP3 receptor inhibits adenylate cyclase by coupling to Gi. 18,19 Nevertheless, the roles of EP subtypes in cell proliferation are different, and could be cell type-dependent. [20][21][22][23][24] To study the role of PGE 2 in myoblast proliferation, the expression of EPs in mouse primary myoblasts was determined showing that all EPs are expressed in myoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…In cancer, the regulation of COX-2 is abolished, so that both enzymes are overexpressed, leading to an increase in prostaglandin (PGE2) production in these cells [42]. PGE2 via stimulation of prostaglandin E2 receptor activates multiple pathways resulting in tumor cell proliferation, angiogenesis, survival and antiapoptosis [43][44][45][46]. In lung cancer cells, particularly in adenocarcinoma, according to clinical studies, overexpression of COX-2 is considered to be a negative predictive factor in the survival of the subpopulation [47].…”
Section: Discussionmentioning
confidence: 99%
“…3, that the EP1 or EP2 receptors were involved in the inhibitory effect of PGE 2 . It is well known that the activation of EP2 increases intracellular cAMP but not EP1 [23]. It was also reported that another type of PAR, PAR1, is downregulated by PGE 2 via EP2 [29].…”
Section: Effect Of Forskolin On Cell Surface Expression and Function mentioning
confidence: 97%